(untitled) (Raparin Journal of Humanities (RJH), 2026)
The paper will address the correlation between employee well-being, pay-for-performance and job satisfaction and job performance of the employees in Sulaimani Municipality in the public sector. The primary goal is to discover which factors have the greatest impact in the determination of job performance here. Data were gathered from 507 employees of the municipal offices in the various departments using a structured questionnaire. The hypothesized relationships were tested with the help of structural equation modeling (SEM).The results indicate that job satisfaction has the most positive effect on job performance followed by employee well-being. Pay-for-performance, however, did not reveal any significant effects, which means that financial incentives may not be as efficient in motivating the employees of the public sector as psychological and emotional factors. The results suggest that it is necessary to establish positive working conditions that will stimulate well-being and satisfaction to enhance performance. The study offers practical recommendations to policy makers and managers who are interested in enhancing employee productivity within the developing country context.